On AI, analytics, and the new machine age (Boston, 2019)
AI and data analytics are powering a wave of technological innovations--understand them, cut through the hype, and seize the opportunities. If you read nothing else on how intelligent machines are revolutionizing business, read these 10 articles. We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you see how these new technologies fit together, understand what's coming next, and prepare your company now. In this book you will learn about how: - Data analytics and AI are yielding insights at an unprecedented rate - Machine learning is reinventing management and reshaping the workforce - Unmanned vehicles are evolving from toys into tools - 3-D printing is moving beyond rapid prototyping to industrial production at scale - Augmented reality is transforming both manufacturing and retail experiences - AI assistants and smart speakers are grabbing territory between customers and brands - A broadly coordinated rollout of blockchain could reshape economies HBR's 10 Must Reads paperback series is the definitive collection of books for new and experienced leaders alike. Leaders looking for the inspiration that big ideas provide, both to accelerate their own growth and that of their companies, should look no further. HBR's 10 Must Reads series focuses on the core topics that every ambitious manager needs to know: leadership, strategy, change, managing people, and managing yourself.
Keywords: Artificial intelligence,Trí tuệ nhân tạo